Effect of Dietary Supplementation of Giloy (Tinospora cordifolia) and Ascorbic Acid along with Different Bedding Materials on Egg Production of Japanese Quail - Poonia, Narender Kumar; Choudhary, Garima; Kumar, Vijay (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
The study investigated the effects of giloy (Tinospora cordifolia) and ascorbic acid supplementation along with different bedding materials (sand B1, saw dust B2 and wheat straw B3) on egg production status of Japanese quails. Total 432 chicks (7 day-old) of Japanese quails were divided into three equal groups (144 each) for different bedding material used and each group was further subdivided into four groups (each of 36 chicks) on the basis of dietary treatment (control T0, giloy T1, ascorbic acid T2 and combination of both T3). Thus birds were randomly and uniformly distributed in total 12 treatment groups comprising of 36 birds in each group and each group was further divided into two replicates comprising 18 birds in each. Quails were fed a basal diet (control, T0) and the basal diet supplemented with giloy 5 g/kg of diet, ascorbic acid 240 mg/kg diet and a combination of giloy 5 g/kg and ascorbic acid 240 mg/kg diet in dietary treatment groups T1, T2 and T3, respectively. Highly significant (p<0.01) effect of incorporation of supplements and different bedding material was found on mean total egg production and egg production per bird of Japanese quail. Total number of eggs produced and egg production per bird were found highest in group on wheat straw bedding material (B3) and on giloy plus ascorbic acid diet combination (T3). The interaction between dietary supplementation and different bedding materials was also highly significant (p<0.01) on total number of eggs produced per flock and per bird. The results showed that a combination of dietary supplements of giloy and ascorbic acid and bedding material wheat straw significantly increased egg production which is beneficial for economics.